Synergistic Effect of TiO₂ Nanorods Incorporated with Graphene Oxide for Photocatalytic Degradation of Multiple Dyes - Bagmita Bhattacharyya; Mithra Geetha; Hayarunissa Anwar; Shabi Abbas Zaidi; Kishor Kumar Sadasivuni; Maimoona Mohamed; Hanan Sheikh; Sarya Muhannad Alfarwati; Rouzait Anwar Jarrar (International Journal of Environmental Research, 2025)
The treatment of dye-contaminated wastewater is essential for mitigating environmental and health risks. In this study, we developed a novel nanocomposite, TiO₂-incorporated graphene oxide (TiO₂@GOn), aimed at enhancing the photocatalytic degradation of neutral red dye, which served as the target analyte. The photocatalysis technique was employed, leveraging the excitation of TiO₂ under UV light to generate reactive oxygen species for efficient dye degradation. TiO₂ nanorods were combined with graphene oxide to form the TiO₂@GOn nanocomposite, designed to improve charge separation and enhance catalytic activity. Nanocomposite characterization was carried out using X-ray diffraction (XRD) to determine crystallographic structure, scanning electron microscopy (SEM) to visualize surface morphology, and UV–Vis spectroscopy to evaluate the optical properties and photocatalytic behavior. The TiO₂@GOn nanocomposite demonstrated a synergistic catalytic effect, outperforming pristine TiO₂ and graphene oxide individually in dye degradation. This study introduces a highly efficient nanomaterial for environmental applications, offering a sustainable approach to the treatment of dye pollutants in wastewater.

Design and Development of Inexpensive Paper-Based Chemosensors for Detection of Divalent Copper - Mithra Geetha; Kishor Kumar Sadasivuni; Maryam Al-Ejji; Nandagopal Sivadas; Bagmita Bhattacharyya; Farzana N. Musthafa; Sarya Alfarwati; Tamanna Jannat Promi; Sumayya Ali Ahmad; Sara Alabed; Dima Anwar Hijazi; Fatimatulzahraa Alsaedi; et al. (Journal of Fluorescence, 2023)
Simple, portable, and low-cost paper-based sensors are alternative devices that have the potential to replace high-cost sensing technologies. The compatibility of the paper base biosensors for both chemical and biochemical accentuates its feasibility for application in clinical diagnosis, environmental monitoring, and food quality monitoring. High concentration of copper in blood serum and urine is associated with diseases like liver diseases, carcinomas, acute and chronic infections, rheumatoid arthritis, etc. Detection of copper concentration can give an early sign of Alzheimer disease. Apart from that genetic Wilson's disease can be detected by evaluating the concentration of copper in the urine. In view of the above advantages, a novel and the highly sensitive paper-based sensor has been designed for the selective detection of Cu 2+ ions. The fast and highly sensitive chemiresistive multi-dye system sensor can detect Cu 2+ ions selectively in as low as 2.23 ppm concentration. Least interference has been observed for counter ion in the detection of Cu 2+ . Copper chloride, nitrate, and acetate were used to validate the detection process. This assay provides a very high selectivity of Cu 2+ ion over other metal cations such as Na + , Mg 2+ , Ca 2+ , etc. The easy preparation and high stability of dye solutions, easy functionalization of the paper-based sensors, high selectivity over other cations, low interference of counter anion, and significantly low detection limit of 2.23 ppm make it an effective Cu 2+ ion sensor for real-time application in near future. Graphical Abstract

Template free synthesis of CuO nanocomposite for catalytic hydrogenation of CO2 - Haseena Onthath; Mostafa H. Sliem; Mithra Geetha; Kishor Kumar Sadasivuni; Aboubakr M. Abdullah; Bijandra Kumar (Journal of Environmental Management, 2023)